Comparative effectiveness of school-based obesity prevention programs for children and adolescents: a systematic review and network meta-analysis - Hassan, Mohamed A.; McDonough, Daniel J.; Ryu, Suryeon; Zhou, Wanjiang; Oginni, John; Gao, Zan (Frontiers in Public Health, 2024)
IntroductionWhile many randomized controlled trials (RCTs) have demonstrated the positive effects of school-based programs in reducing body fat among children and teenagers, there is no conclusive evidence to indicate that one approach is superior to another, largely due to the lack of direct and indirect comparisons. This study evaluated the relative effectiveness of various school-based obesity prevention initiatives in improving body mass index (BMI) among children and adolescents using network meta-analysis.MethodsSearches included four databases focusing on articles published in English between the years 2002 and 2024. The primary outcomes were the BMI and BMI z-scores (BMIz) (kg/m2). The mean differences (MDs) for each outcome were calculated before and after treatment. The current systematic review synthesized 53 RCTs with a sample of 68,489 children and adolescents.ResultsThe results illustrated that the physical activity (PA) only arm was the most effective intervention in improving BMI (MD: −0.42, 95% credible interval (Crl) −0.79, −0.07; p = 0.02), while the multiple-component intervention was the most effective in improving BMIz (MD: −0.08, 95% Crl: −0.16, −0.01; p = 0.03). Inversely, PA and another component arm were the least effective interventions in improving BMI (MD: 0.64, 95% Crl: −0.23, 1.53; p = 0.15). In addition, diet and nutrition only arm was the least effective intervention in improving BMIz (MD: 0.09, 95% Crl: −0.11, 0.28; p = 0.36).DiscussionIn conclusion, both PA-only and multiple-component arms are effective intervention tools/strategies for reducing BMI-related outcomes. However, further large-scale, well-designed studies are needed to investigate the elements of multiple-component arms.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/ identifier CRD42021234742.